2021
DOI: 10.3390/diagnostics11122242
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Prolonged Length of ICU Stay through Machine Learning

Abstract: This study aimed to construct machine learning (ML) models for predicting prolonged length of stay (pLOS) in intensive care units (ICU) among general ICU patients. A multicenter database called eICU (Collaborative Research Database) was used for model derivation and internal validation, and the Medical Information Mart for Intensive Care (MIMIC) III database was used for external validation. We used four different ML methods (random forest, support vector machine, deep learning, and gradient boosting decision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 73 publications
1
21
0
1
Order By: Relevance
“…Thus, using a relatively narrow time window, which is 24 h, to predict long-term outcomes theoretically resulted in a weak predictive capability. However, the result is still competitive in all three outcome predictions because of the application of deep learning models with a small quantity of time-series variables ( 8 , 9 , 31 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, using a relatively narrow time window, which is 24 h, to predict long-term outcomes theoretically resulted in a weak predictive capability. However, the result is still competitive in all three outcome predictions because of the application of deep learning models with a small quantity of time-series variables ( 8 , 9 , 31 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, traditional scoring systems, even some machine learning methods in predicting these outcomes, especially in stratifying the risk of readmission, have shown only modest results (7)(8)(9)(10). Although part of the existing work based on machine learning models seems promising (11)(12)(13), few of them are able to take advantage of the characteristics of features collected in the ICU, which are time-series forms.…”
Section: Introductionmentioning
confidence: 99%
“…Length of stay has also been studied to predict the length of stay in the context of traumatic brain injury (TBI), 39 predictions were also made using patient vital signs 40 as well as a gradient boosted decision trees algorithm trained using data available in the eICU and MIMIC III datasets. 41 A model was able to predict readmission from information in the MIMIC III dataset significantly better than both the Stability and Workload Index for Transfer score (AUC = .65) and the Modified Early Warning Score (AUC = .58), with an AUC of .76. 42 While more work is clearly needed, these studies nonetheless provide a proof of concept for how future versions of these models could benefit intensivists.…”
Section: Length Of Stay and Readmissionmentioning
confidence: 92%
“…Additionally, the accurate prediction of LOS may allow hospitals to increase capacity and better predict healthcare costs [16]. Previous studies have reported numerous predictive scores for LOS using machine learning (ML) techniques; some have analysed patients who underwent coronary artery bypass grafting [17,18] and others those with critical illnesses [19,20]. However, the majority of reported predictions have been developed with clinical data gathered at the time of initial hospitalisation [19,20] or during surgery [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported numerous predictive scores for LOS using machine learning (ML) techniques; some have analysed patients who underwent coronary artery bypass grafting [17,18] and others those with critical illnesses [19,20]. However, the majority of reported predictions have been developed with clinical data gathered at the time of initial hospitalisation [19,20] or during surgery [17,18]. Little research has focused on predictive outcomes for individuals with sepsis.…”
Section: Introductionmentioning
confidence: 99%